A glucose modified filter paper for effective oil/water separation. Issue 52 (21st August 2018) - Luo, Zhonglin; Duan, Cong; Li, Yan; Wang, Yanbin; Wang, Biaobing
Abstract : Toluene/water emulsion cannot be separated by the un-treated filter paper. In comparison, toluene/water emulsion could be efficiently separated by the glucose (GLC) treated filter paper. Abstract : Efficient and low-cost oil/water separation remains a great challenge for industries. Natural cellulose-based filter paper, because of its abundance, low cost, biodegradability and excellent chemical stability, has been developed as an oil/water separator in recent years. In the present study, a superhydrophilic and underwater superoleophobic filter paper is successfully prepared by an aldol condensation reaction to crosslink glucose molecules with filter paper. The prepared filter paper is characterized by IR-spectroscopy, SEM spectroscopy and wettability measurements, and it has high underwater oil contact angles of over 162° for hexane, toluene and petroleum ether. It is shown that the modified filter paper has high water recovery from various oil/water mixtures, not only in a gentle environment but also in acidic, alkaline, and salty environments and at different temperatures. Moreover, the glucose modified filter paper shows excellent oil/water emulsion separation efficiency (>99%) and good recycling performance. The preparation is economic and could be easily scaled up, suggesting its great potential for large-scale industrial applications.